Setting Strategic Priorities of Floss Marketing Mix in SME “Raja Abon Makmur Lestari”, Pangkalpinang - Yulia Yulia; Novyandra Ilham Bahtera; Rati Purwasih (Journal La Bisecoman, 2020)
Raja Abon Makmur Lestari (RAML) is a home industry that produces a various types of flosses both from animal and vegetable. In terms of marketing, the owner faces obstacle such as the fluctuated sales, lack of manpower, unachieved targeted turnover, as well as the high competitiveness in the industry. Thus, the marketing strategic is required to solve the issue. Marketing mix is one of the ways as the marketing strategic to create purchasing decision on the consumers. Case study was used as the approach of the study. The owner and the consumer were the respondent of the study. Quantitative strategic planning matrix (QSPM) was used as a data analysis method. It was used to determine marketing strategic priority based on the internal decision. The descriptive analysis was also used to evaluate the marketing mix. The study found that the marketing mix priority was put in order: promotion, product, place, and price. Furthermore, the priority of sub promotion mix was direct marketing, public relation, mass media and social media. The study was beneficial for the RAML to determine future marketing strategic so that the goals setting will be achieved effectively and efficiently.